Manajemen Data Dalam Sistem Informasi Mutaaba’ah Tahfidz - Rohimah, Lanny Suryani (Journal of Comprehensive Science, 2025)
Digital transformation in the education sector has expanded the application of information technology in learning processes, including Qur’an memorization (tahfidz) programs. This study analyzes data management in the mutaaba’ah tahfidz information system, with a case study on the mutaaba’ah tahfidz Al-Qur’an application at SMP IT Al-Khoiriyyah. Using a qualitative approach and document study based on research [1], the analysis focuses on data structure, information flow, data quality, security, and utilization. The findings indicate that the system successfully replaced manual recording with MySQL-based digital storage integrated with a Java interface, enabling structured reporting of memorization progress. However, weaknesses were identified in data validation, access control, and database design, which has not yet been fully normalized. Based on the DAMA-DMBOK framework, recommendations include the implementation of data governance, audit trails, and data visualization to enhance quality, security, and informational value. This study provides strategic guidance for the development of sustainable, accountable, and measurable religion-based educational information systems.